MODELS OF SLEWING HOISTING MACHINERY (Perner's Contacts, 2017)
This entry describe of a model two hoisting machineries. In this entry is more detailed describe engineering design and realization by the standing derrick, which is recess crane trolley by lifting device, created as suspender by crane trolley.
Keywords: crane trolley; standing derrick; hoisting machinery